Novel plasma-assisted low-temperature-processed SnO2 thin films for efficient flexible perovskite photovoltaics - Subbiah, Anand S. (2020)
The recent evolution of solution-processed hybrid organic–inorganic perovskite-based photovoltaic devices opens up the commercial avenue for high-throughput roll-to-roll manufacturing technology. To circumvent the thermal limitations that hinder the use of metal oxide charge transport layers on plastic flexible substrates in such technologies, we employed a relatively low-power nitrogen plasma treatment to achieve compact SnO2 thin-film electrodes at near room temperature. The perovskite photovoltaic devices thus fabricated using N2 plasma-treated SnO2 performed on par with thermally annealed SnO2 electrodes and resulted in a power conversion efficiency (PCE) of ca. 20.3% with stabilized power output (SPO) of ca. 19.1% on rigid substrates. Furthermore, the process is extended to realize flexible perovskite solar cells on indium tin oxide (ITO)-coated polyethylene terephthalate (PET) substrates with champion PCE of 18.1% (SPO ca. 17.1%), which retained ca. 90% of its initial performance after 1000 bending cycles. Our investigations reveal that deep ultraviolet irradiation associated with N2 and N2O plasma emission plays a major role in obtaining good quality metal oxide thin films at lower temperatures and offers promise toward facile integration of a wide variety of metal oxides on flexible substrates.